Grandad Bill's Song - Jane Yolen (Hong Kong Philomel Books, 1994)
The author of Owl Moon calls on her own experience for this lyrical poem about a young child seeking to express his feelings after the death of his grandfather.
Keywords: Circle Time Book - Faith / Spirituality / Healing -- Circle Time Book - Faith / Spirituality / Healing